Using fuzzy logic to control vehicles velocity in traffic system - Alghamdi, A.; Eren, Halit (2013)
Approaching the desired vehicle speed by using a FUZZY logic controller is the goal of this article. It provides a controller that both increases and decreases in velocity). The lead vehicle and the follow vehicle have the same input variables, such as velocity or velocity error, acceleration factor, reaction factor (a), and deceleration factor (ß), while the bumper-to-bumper gap (Xrel) is not important for the lead vehicle. The relation between inputs and output is discussed. This paper explains a novel approach to the simulation of a congestion system by using a closed-loop system for 69 vehicles. This work will continue to solve the congestion problem.